AYURVEDA AND MENTAL HEALTH - DEEKSHITULU P.V, BALAJI (Innovare Journal of Ayurvedic Sciences, 2014)
The review article explains Ayurveda has its own identity as most ancient and traditional System of Medicine in India. Ayurveda is perfect balance of mind, body and soul as complete health in human beings. Ayurveda aims at preservation and promotion of heath, and prevention and cure of diseases through the concepts of positive physical and mental health. Ayurveda is good Management of mental health